FORMATION OF ORAL SPEECH OF CHILDREN WITH HEARING IMPAIRMENTS - Abdullayeva Nargiza O‘ktamovna (Journals Park Publishing, 2022)
The article talks about the formation of oral speech in children with hearing impairments and the use of innovative techniques in their teaching. Engaging and educating children with hearing impairments will open the door to wider opportunities for them to achieve success in the future, among other peers in the society.
Keywords: defectologia; children; voice